Early peritoneal immune response during Echinococcus granulosus establishment displays a biphasic behavior. - Gustavo Mourglia-Ettlin; Juan Martín Marqués; José Alejandro Chabalgoity; Sylvia Dematteis (Public Library of Science (PLoS), 2011)
BACKGROUND: Cystic echinococcosis is a worldwide distributed helminth zoonosis caused by the larval stage of Echinococcus granulosus. Human secondary cystic echinococcosis is caused by dissemination of protoscoleces after accidental rupture of fertile cysts and is due to protoscoleces ability to develop into new metacestodes. In the experimental model of secondary cystic echinococcosis mice react against protoscoleces producing inefficient immune responses, allowing parasites to develop into cysts. Although the chronic phase of infection has been analyzed in depth, early immune responses at the site of infection establishment, e.g., peritoneal cavity, have not been well studied. Because during early stages of infection parasites are thought to be more susceptible to immune attack, this work focused on the study of cellular and molecular events triggered early in the peritoneal cavity of infected mice. PRINCIPAL FINDINGS: Data obtained showed disparate behaviors among subpopulations within the peritoneal lymphoid compartment. Regarding B cells, there is an active molecular process of plasma cell differentiation accompanied by significant local production of specific IgM and IgG2b antibodies. In addition, peritoneal NK cells showed a rapid increase with a significant percentage of activated cells. Peritoneal T cells showed a substantial increase, with predominance in CD4(+) T lymphocytes. There was also a local increase in Treg cells. Finally, cytokine response showed local biphasic kinetics: an early predominant induction of Th1-type cytokines (IFN-γ, IL-2 and IL-15), followed by a shift toward a Th2-type profile (IL-4, IL-5, IL-6, IL-10 and IL-13). CONCLUSIONS: Results reported here open new ways to investigate the involvement of immune effectors players in E. granulosus establishment, and also in the sequential promotion of Th1- toward Th2-type responses in experimental secondary cystic echinococcosis. These data would be relevant for designing rational therapies based on stimulation of effective responses and blockade of evasion mechanisms.